THE CONCEPT OF “SPIRITUAL SPACE” AND ITS CONTENT AND ESSENCE - Mamatkulov Eldor Safarovich (Western European Studies, 2025)
This article explores the concept of “spiritual space” and its essence from a philosophical perspective. It examines the theoretical foundations, historical development, and socio-cultural significance of spiritual space in shaping human consciousness, moral values, and personal identity. The study highlights how spiritual space functions as an internal and external framework for ethical behavior, self-realization, and the formation of cultural and religious values. By analyzing classical and contemporary philosophical sources, the article emphasizes the multidimensional nature of spiritual space and its role in guiding individuals toward a balanced, meaningful life
Keywords: Spiritual space; philosophical concept; human consciousness